Recovery potential of Arctic wetland tundra on Svalbard. Long-term impacts of grazing by barnacle geese (Branta leucopsis) within the context of climate change - Paquin, Karolina (UiT Norges arktiske universitet, 2014)
The substantial increase of the migratory Svalbard population of Barnacle geese Branta leucopsis during the past 50 years has been attributed to a warming climate, changes in agricultural land use, and conservation measures. The geese are likely to continue to forage and reproduce in Arctic wetlands in increasing numbers. This project revisited the experimental plots from an earlier experiment (FRAGILE) on goose grazing and climate warming to assess the long-term recovery potential of wet tundra plant communities from the grazing disturbance applied 8 years prior. Recovery was defined as comparable above ground biomass and community composition of control and grazed treatments, and it was expected to detect the influence of high grazing pressure, and for this response to differ under warmed conditions. Grazing and OTCs were combined in a fully factorial design, with 3 summers of grazing pressure applied using captured barnacle geese to simulate natural and high applied, and 10 years of simulated conditions of climate warming using OTCs. OTCs increased the air temperature, but decreased the soil temperature. In ambient treatment, no effect of grazing was detected for the functional groups but biomass responded positively to 5 hour grazing treatment. In OTCs, the biomass responded positively in 1 hour treatment, functional groups pteridophytes and graminoids responded positively in all grazing levels, and bryophytes only in ungrazed. Presence of rarer species fluctuated over the years, while the dominant forage species Dupontia sp, Eriophorum scheuchzeri, Cardamine nymanii, Equisetum arvense and Calliergon richardsonii have remained ubiquitous in all years. Thus, the positive impact of grazing on biomass and response of certain functional groups was still detectable eight years after intense goose grazing and ten years of continuous warming, suggesting that Arctic tundra wetlands are slow to recover from intensified grazing disturbance.